The Influence of Live Streaming, Content Marketing, and Online Customer Reviews on Purchase Decisions (A Study on TikTok Shop Ceilo Official) - Gita Mardhatilla Noviarafita; Lia Nirawati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the influence of Live Streaming, Content Marketing, and Online Customer Review on Purchasing Decisions in purchases via E-commerce on the TikTok Shop application. With a focus on ceilo official followers the method used in this study is associative with a quantitative approach. Data was collected through a questionnaire distributed to 98 respondents with a purposive sampling technique. The results of the study indicate that Live Streaming has a positive and significant effect on Purchasing Decisions. Content Marketing has a positive and significant effect on Purchasing Decisions. However, Online Customer Review does not have a significant effect partially on Purchasing Decisions. However, simultaneously, the three variables have a significant effect on Purchasing Decisions on Ceilo official TikTok Shop.